2021
DOI: 10.1097/md.0000000000023641
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Bacillus coagulans LBSC in irritable bowel syndrome

Abstract: Goals: To evaluate safety and efficacy of Bacillus coagulans LBSC [DSM17654] in irritable bowel syndrome (IBS) through a prospective, interventional, randomized, double-blind, and placebo-controlled, CONSORT compliant clinical trial. Background: Bacteriotherapy shows promising impact on alleviating clinical conditions of IBS and associated functional gastrointestinal disorders. B coagulans LBSC is a genetically and phenotypically safe probiotic strain u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 43 publications
1
34
0
2
Order By: Relevance
“…The studies were published between 2005 and 2021. Most studies were conducted in Europe (n = 19; 54%) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], followed by Asia (n = 11; 31%) [41][42][43][44][45][46][47][48][49][50][51], America (n = 4; 11%) [52][53][54][55] and Africa (n = 1; 3%) [56]. In total, the 35 trials included 4717 participants.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies were published between 2005 and 2021. Most studies were conducted in Europe (n = 19; 54%) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], followed by Asia (n = 11; 31%) [41][42][43][44][45][46][47][48][49][50][51], America (n = 4; 11%) [52][53][54][55] and Africa (n = 1; 3%) [56]. In total, the 35 trials included 4717 participants.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
“…In total, the 35 trials included 4717 participants. The median age was 42 [41][42][43][44][45][46] years and 68% of the participants were women. The duration of the interventions ranged between 4 and 24 weeks with a median length of 7 [5.5-8] weeks.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
“…Most of the above-described studies are focused on all IBS subtypes [ 80 , 81 , 82 , 87 , 88 , 89 , 95 , 100 , 108 , 109 , 112 , 113 , 115 , 116 , 118 , 119 , 120 ]. Although, several studies did not differentiate the form of the disease among participants [ 79 , 83 , 84 , 85 , 90 , 91 , 92 , 96 , 101 , 103 , 104 , 127 ]. Moreover, Oh et al (2019) performed the analysis of probiotic impact on IBS patients with the exclusion of subjects suffering from IBS-C [ 124 ].…”
Section: Probiotics Prebiotics and Synbiotics In Ibs Treatmentmentioning
confidence: 99%
“…This probiotic improved symptoms of IBS only among individuals suffering from the IBS-D subtype[100]. Other effective probiotics in improving IBS symptoms are strains of Bacillus coagulans[101][102][103][104] Majeed et al (2018). observed that B. coagulans MTCC 5856 could reduce sleeplessness and depression in IBS-D patients[102].Gupta et al (2012) noted the beneficial impact of B. coagulans LBSC on GIT microbiota of IBS individuals[104].…”
mentioning
confidence: 99%
See 1 more Smart Citation